2022
DOI: 10.1111/crj.13478
|View full text |Cite
|
Sign up to set email alerts
|

The alterations of retinal vasculature detected on optical coherence tomography angiography associated with chronic obstructive pulmonary disease

Abstract: Objectives This study aimed to evaluate the retinal vasculature of the macula and optic disc in patients with chronic obstructive pulmonary disease (COPD) by optical coherence tomography angiography (OCTA). Methods The right eyes of 70 COPD patients and 71 healthy individuals were evaluated. These patients had moderate airflow limitation and mean PO2 of 60 mmHg, and their average age was less than 60 years. Superficial and deep capillary plexus vascular densities, foveal avascular zone (FAZ) width, and optic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…A possible explanation for the vulnerability of the DCP in ischemia could be the distance from the bigger retinal arteries and the proximity to the outer retina which has bigger metabolic requirements due to the photoreceptors and retinal pigment epithelium's activity. In addition, patients that suffer from chronic obstructive pulmonary disease or sleep apnea syndrome have been found to have decreased retinal VD, implying that oxygenation plays an important role in macular microvascular damage [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the vulnerability of the DCP in ischemia could be the distance from the bigger retinal arteries and the proximity to the outer retina which has bigger metabolic requirements due to the photoreceptors and retinal pigment epithelium's activity. In addition, patients that suffer from chronic obstructive pulmonary disease or sleep apnea syndrome have been found to have decreased retinal VD, implying that oxygenation plays an important role in macular microvascular damage [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reporting retinal blood flow alterations in systemic disease ( 29 , 30 , 33 35 ), Kannenkeril et al also indicate that OCTA changes are associated with disease progression in CKD ( 31 ), showing promise as a marker of disease severity in other systemic disorders affecting the microcirculation. Coppolino et al ( 32 ) found an association between pre-dialysis retinal VD and patients who subsequently experienced intradialytic hypotension, demonstrating prognostic value and concluding that OCTA could stratify the short-term risk of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic obstructive pulmonary disorder (COPD) had reduced retinal vascular density compared with healthy controls in the superficial and deep capillary plexi on OCTA ( p = 0.002) ( 35 ). COPD patients also had a larger FAZ diameter than healthy participants ( p = 0.002) ( 35 ), and there was a moderate correlation between partial pressure of oxygen (pO 2 ) and superficial/deep vascular density ( r = 0.559/0.800 respectively), and a highly negative correlation between pO 2 and FAZ size ( r = −0.876) ( 35 ), suggesting that retinal vascular density by OCTA may be useful to monitor disease progression in COPD patients ( 35 ). Retinal imaging in COPD has also shown that older age, higher systolic BP and lower levels of systemic inflammation are associated with narrower retinal venules ( p < 0.05) ( 36 ).…”
Section: Systemic Disturbances and Retinal Blood Flow In Non-septic S...mentioning
confidence: 99%